Systematic Literature Review of Integrated Tourism Information Systems for Effective Destination Management - Okta Veza; Nofri Yudi Arifin (YCMM, 2025)
The rapid development of digital technology has significantly transformed the tourism sector into a data-driven ecosystem, where information plays a crucial role in supporting destination management. This study aims to analyze the development and role of Integrated Tourism Information Systems (ITIS) in improving the effectiveness of destination management through a Systematic Literature Review (SLR) approach. The review was conducted on selected articles published between 2023 and 2025 from reputable international databases.The findings indicate that ITIS contributes to enhancing data integration, operational efficiency, and decision-making processes within tourism ecosystems. However, most existing studies still focus on partial system integration and face challenges related to interoperability, data management, and system adaptability. In addition, advanced technologies such as artificial intelligence (AI), Internet of Things (IoT), and big data analytics have not been fully optimized in tourism applications.The study also reveals a significant research gap, where integrated systems in tourism are still limited compared to other domains. Therefore, future research is recommended to develop more integrated, adaptive, and user-centered tourism information systems. This study provides both theoretical and practical contributions to the development of digital tourism management.